The effect of genotype on anther culture response of cultivated and wild oats - Kiviharju, Elina; Puolimatka, Matti; Saastamoinen, Marketta; Hovinen, Simo; Pehu, Eija (Agricultural and Food Science, 1998)
Anther culture ability was tested for 44 oat (Avena sativa L.), six naked oat (A. sativa L., naked type) and 15 wild oat (Avena sterilis L.) genotypes, in addition to progeny of five intraspecific crosses of A. sativa and two interspecific crosses of A. sativa x A. sterilis. Anther culture response was affected considerably by genotype. Thirty one oat genotypes responded by callus growth on induction medium and seven of them produced embryo structures, two of the lines consistently. All naked oat genotypes produced embryo structures. Embryo production rates for the wild oat lines were comparable with those for the naked oat genotypes, and higher than for oat: 13 of the 15 genotypes tested produced embryo structures. Plant regeneration was possible only from wild oat. The regeneration ability was inherited in the progeny of the A. sativa x A. sterilis cross cv. Puhti x CAV 2648. The response of anthers of oat genotypes was inhibited by auxin on the induction medium, while naked oat, wild oat and A. sativa x A. sterilis crosses responded better on a medium containing 2,4-dichlorophenoxyacetic acid.